2012
DOI: 10.1016/j.bmc.2011.10.080
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines and benzotriazepines as protein interaction inhibitors targeting bromodomains of the BET family

Abstract: Graphical abstractA number of triazolo-benzodiazepines including drugs such as alprazolam have been developed as protein interaction inhibitors that target bromodomains of the BET family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 38 publications
4
111
1
Order By: Relevance
“…50 Notably, the widely prescribed anxiolytic alprazolam (21) bound to BRD4(1) with a K D of 2.5 μM [cf. 0.05 μM for (+)-2] ( Figure 8A,B); however, the authors note that this affinity means that it is unlikely that alprazolam has any effect on bromodomains at clinically relevant doses.…”
Section: Family Of Bromodomainsmentioning
confidence: 99%
“…50 Notably, the widely prescribed anxiolytic alprazolam (21) bound to BRD4(1) with a K D of 2.5 μM [cf. 0.05 μM for (+)-2] ( Figure 8A,B); however, the authors note that this affinity means that it is unlikely that alprazolam has any effect on bromodomains at clinically relevant doses.…”
Section: Family Of Bromodomainsmentioning
confidence: 99%
“…We found that benzo-diazepine and benzo-triazepine scaffolds exhibit affinity for BET BRDs providing good starting points for rational inhibitor design [99]. We developed a cell-permeable and potent inhibitor (JQ1), based on a triazolo-thieno-diazepine scaffold with high affinity and selectivity for all BET BRDs [19].…”
Section: Inhibition Of Brd-specific K Ac Readoutmentioning
confidence: 99%
“…A striking example of the effect of JQ1 is its ability to control male fertility via reversible inhibition of the testis-specific protein BRDT in mice [54]. Notably, some drugs currently on the market can also bind bromodomains, as recently demonstrated for alprazolam and midazolam [55], but the importance of these interactions in their therapeutic effects is unknown.…”
Section: Epidrugsmentioning
confidence: 96%